2019
DOI: 10.1055/a-0977-2777
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal involvement in patients with vasculitis: IgA vasculitis and eosinophilic granulomatosis with polyangiitis

Abstract: Background and study aims  Among vasculitides, IgA vasculitis (IgAV) and eosinophilic granulomatosis with polyangiitis (EGPA) frequently damage the gastrointestinal tract. However, only a few studies have investigated the entire gastrointestinal tract in patients with IgAV or EGPA by endoscopy. The aim of this study was to clarify endoscopic characteristics of patients with IgAV and those with EGPA. Patients and methods  Clinicopathological and endoscopic findings were retrospectively compared between 33 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…It seems difficult to make a diagnosis of PNH by endoscopic biopsy; nonetheless, gastrointestinal biopsy may be beneficial in differentiating PNH from IgA vasculitis, which can present with both gastric patchy redness and duodenal ulcer. 19,20 Treatment with corticosteroids, proton-pump inhibitors, and diet control was successful in our patient. Various treatments have been reported for PNH-related thrombosis.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It seems difficult to make a diagnosis of PNH by endoscopic biopsy; nonetheless, gastrointestinal biopsy may be beneficial in differentiating PNH from IgA vasculitis, which can present with both gastric patchy redness and duodenal ulcer. 19,20 Treatment with corticosteroids, proton-pump inhibitors, and diet control was successful in our patient. Various treatments have been reported for PNH-related thrombosis.…”
Section: Discussionmentioning
confidence: 69%
“…The patchy areas of gastric redness present in our patient have not been reported so far. It seems difficult to make a diagnosis of PNH by endoscopic biopsy; nonetheless, gastrointestinal biopsy may be beneficial in differentiating PNH from IgA vasculitis, which can present with both gastric patchy redness and duodenal ulcer 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…Second line treatments, such as the use of mycophenolate mofetil, intravenous cyclophosphamide or intravenous immunoglobulin, as well as endoscopic haemostasis, were not used since all patients with GI bleeding favourably responded to therapy with glucocorticoids, similar to many other studies. 41 Although glucocorticoids have been shown to be very successful in treating our patients with severe gastrointestinal journals.sagepub.com/home/tab 11 manifestations, they have not influenced the risk of developing late-onset IgAVN, and similar results have been shown in controlled studies, therefore prophylactic use of glucocorticoids in IgAVN prevention is not indicated. 40 In patients who were treated with glucocorticoids because of GI manifestations we have observed higher chance for early-onset IgAVN, probably due to the previously explained association between GI symptoms and renal disease, in that more pronounced inflammatory response results in more severe GI manifestations and, consequently, by still insufficiently elucidated mechanisms, it also leads to increased local inflammation in the kidneys.…”
Section: Discussionmentioning
confidence: 89%
“…14 Although some studies have explored endoscopic findings of GI disease in other vasculitides, because of the rarity of GPA in the GI tract, most of the work in this area has focused on the widely varying GI manifestations of GPA. 15 Currently, neither the American College of Rheumatology nor the American College of Gastroenterology has guidelines on the endoscopic diagnosis or medical management of GI manifestations of GPA. 16 Our patient's young diagnosis age, ANCA negativity, and GI manifestations are unusual for GPA.…”
Section: Discussionmentioning
confidence: 99%